Prognostic Significance of Focal Adhesion Kinase in Node-Negative Breast Cancer - Almstedt, Katrin (Breast Care (Basel), 2017)
BACKGROUND: Focal adhesion kinase (FAK) is a cytoplasmic tyrosine kinase that plays an important role as a mediator of cell migration, invasion, proliferation and survival. Conflicting results for the prognostic role of FAK in breast cancer (BC) prompted us to determine its impact. METHODS: Patients with node-negative BC entered this retrospective study. FAK expression was determined by immunohistochemistry (n = 335). The prognostic impact of FAK was examined with Cox regression analyses and Kaplan-Meier estimation in the whole cohort as well as in different molecular subtypes. RESULTS: 151 (45.1%) had a FAK-positive BC. In univariate analyses, FAK expression showed a significant impact for shorter disease-free survival (DFS) (hazard ratio (HR) 1.54, 95% confidence interval (CI) 1.04–2.28, p = 0.030) but not for metastasis-free survival and overall survival. Significant prognostic relevance for DFS (HR 1.76, 95% CI 1.05–2.97, p = 0.033) was observed in particular in estrogen receptor-positive HER2-negative BC patients, most notably in luminal B-like tumors (HR 2.32, CI 1.20–4.48, p = 0.012). However, FAK lost its prognostic impact in multivariate Cox regression analysis. CONCLUSION: FAK was associated with impaired DFS in univariate analysis. Prognostic relevance for DFS was most pronounced in luminal B-like BC. However, FAK expression was not associated with an independent impact on survival for BC in multivariate analysis.